Long-term exposure to traffic-related air pollution is associated with impaired odor identification: Results from the population-based KORA FIT study in Augsburg, Germany - Nikolaos Nikolaou; Kathrin Wolf; Susanne Breitner; Regina Pickford; Tamara Schikowski; Annette Peters; Alexandra Schneider (Environment International)
Ambient air pollution has been linked to neurodegenerative diseases. Nevertheless, the literature on the effects of air pollution on the olfactory system and early cognitive impairment is scarce. In this study, we investigated the association between long-term air pollution exposure and odor identification, which can serve as an early indicator of various neurodegenerative conditions. We used data collected in Augsburg, Germany in 2018–2019 for the population-based KORA FIT study of 3,059 participants born between 1945–1964. The Sniffin’ Sticks 12-Item Test was used to assess each participant’s odor identification. Air pollution concentrations at residential addresses were estimated using land use regression modeling. We dichotomized the odor identification score to normosmia (score ≥ 10) versus hyposmia (score < 7) or anosmia (score < 10) and applied logistic regression. The models were adjusted for age, sex, socioeconomic characteristics (education, income, socioeconomic status), lifestyle factors (physical activity, smoking, body mass index, alcohol consumption) and disease history (e.g., allergies). We observed increased odds of hyposmia or anosmia compared to normosmia per interquartile range increase in the concentrations of PNC, PM2.5, PM2.5abs, PMcoarse, PM10, NO2 and NOx [OR (95 % CI): 1.12 (1.02, 1.24), 1.10 (0.98, 1.25), 1.14 (1.00, 1.30), 1.20 (1.06, 1.35), 1.20 (1.06, 1.36), 1.20 (1.06, 1.37) and 1.13 (1.01, 1.27); respectively]. For O3, no clear effects were detected. Females and physically active people appeared to be more susceptible. No further significant indications of effect modification were found. The results were consistent across sensitivity analyses. This study provides robust evidence for an association between long-term exposure to traffic-related air pollution and poor odor identification, even in a region with relatively low air pollution levels. These findings suggest a potential link between prolonged air pollution exposure and early changes in the olfactory system and could be indicative of early signs of detrimental effects on the brain.